Numerical Study on the Performance of a Cogeneration System of Solid Oxide Fuel Cell Based on Biomass Gasification - Dang, Zheng; Jiang, Zhaoyi; Ma, Jinyan; Shen, Xin; Xi, Guang (Frontiers in Energy Research, 2021)
In order to solve the environmental pollution problem caused by winter heating of rural residential building in northern of China, in this paper a biomass gasification (BG)-solid oxide fuel cell (SOFC) combined heating and power (CHP) system has been establishedand numerically investigated. Taking a rural village around Xi'an which is an ancient city and located at central of northern China as the study object, according to heat and electricity output of the system and the heating and electrical load characteristics of the residential building of village, the energy saving ratio and economical efficiency of the CHP system under three different operation schemes compared with the traditional energy system have been analyzed. The results show that the operation scheme for heating designated rooms in rural buildings and meeting the average heat demand of users is the most energy-efficient and economical way. The primary energy saving rate and annual cost saving rate can reach 18.0% and 10.3%, respectively. When the user's heat and power load demand is clear, the closer the system's output heat and power ratio to the user's heat and power load ratio, the more significant the system's energy saving effect.